Antibiotic Resistance of Escherichia coli Isolated from Proboscis Monkey Feces at Surabaya Zoo - Zahrania Marsha Amira Sulherman; Yulianna Puspitasari; Wiwiek Tyasningsih (Journal of Basic Medical Veterinary, 2026)
Antimicrobial resistance (AMR) is a growing concern affecting both human and veterinary medicine. Escherichia coli is commonly used as an indicator organism for evaluating antibiotic resistance because of its ability to acquire and disseminate resistance genes. Captive wildlife, such as non-human primates, may act as reservoirs of resistant bacteria at the human–animal interface. This study aimed to determine the antibiotic resistance patterns of E. coli isolated from the feces of proboscis monkeys (Nasalis larvatus) at Surabaya Zoo, Indonesia. A descriptive laboratory-based study was conducted using 13 E. coli isolates obtained from fresh fecal samples. Antimicrobial susceptibility testing was performed using the Kirby–Bauer disk diffusion method according to Clinical and Laboratory Standards Institute (CLSI) guidelines. The antibiotics tested included amoxicillin, trimethoprim/sulfamethoxazole, ceftazidime, levofloxacin, and tetracycline. Isolates resistant to three or more classes of antimicrobials were classified as multidrug-resistant (MDR). All isolates (100%) were resistant to amoxicillin and ceftazidime. Resistance to levofloxacin was observed in 23.1% of isolates, whereas resistance to trimethoprim/sulfamethoxazole and tetracycline was each observed in 15.4% of isolates. Overall, 38.5% of the isolates were classified as MDR. The high prevalence of β-lactam resistance and the presence of multidrug-resistant E. coli in captive proboscis monkeys suggest that zoological institutions may serve as reservoirs of antimicrobial resistance.